Indices de similitud entre taxocenosis de t1ebótomos (Diptera: Psychodidae) en un área endémica de leishmaniasis cutánea en Costa Rica - Herrero, Marco V (1993)
A comparison of diversity between eight Costa Rican taxocenosis of phlebotorninae sandflies was made with the Sorensen sirnilarity coefficient. Sites Agua Blanca-Chirraca (C = 0.68), Ceiba Este-Chirraca (C = 0.66), La Montaña--Chirraca (C = 0.62) and La Montaña-Hondouada (C = 0.68) are very similar in species composition and aboodance. Linda V ista and OCoca are significantly different from other localities